Five layers of receptor signalling in γδ T cell differentiation and activation - Ribeiro, Sérgio T.; Ribot, Julie C.; Silva-Santos, Bruno (Frontiers in Immunology, 2015)
The contributions of gamma-delta T cells to immunity to infection or tumours critically depend on their activation and differentiation into effectors capable of secreting cytokines and killing infected or transformed cells. These processes are molecularly controlled by surface receptors that capture key extracellular cues and convey downstream intracellular signals that regulate gamma-delta T cell physiology. The understanding of how environmental signals are integrated by gamma-delta T cells is critical for their manipulation in clinical settings. Here we discuss how different classes of surface receptors impact on human and murine gamma-delta T cell differentiation, activation and expansion. In particular, we review the role of five receptor types: the T cell receptor (TCR), costimulatory receptors, cytokine receptors, NK receptors and inhibitory receptors. Some of the key players are the costimulatory receptors CD27 and CD28, which differentially impact on pro-inflammatory subsets of gamma-delta T cells; the cytokine receptors IL-2R, IL-7R and IL-15R, which drive functional differentiation and expansion of gamma-delta T cells; the NK receptor NKG2D and its contribution to gamma-delta T cell cytotoxicity; and the inhibitory receptors PD-1 and BTLA that control gamma-delta T cell homeostasis. We discuss these and other receptors in the context of a five-step model of receptor signalling in gamma-delta T cell differentiation and activation, and discuss its implications for the manipulation of gamma-delta T cells in immunotherapy.